Pengaruh Kemampuan Komunikasi Guru dan Keaktifan Siswa Terhadap Kepuasan Belajar Siswa Pada Mata Pelajaran Kewirausahaan Kelas X SMK Muhammadiyah 01 Sambi Kabupaten Boyolali Tahun 2015/2016 - Serviana, Yesi; , Drs. Muhammad Yahya, M.Si (2016)
The purpose of this research are: 1) To determine whether there is influence communication skills of teachers to student learning satisfaction. 2) To determine whether there is influence activity of students to satisfaction of student learning. 3) To determine whether there is influence communication skills teacher and studen activity together to satisfaction of student learning. This research is descriptive research with quantitative approach to statistical inference through motode conducted on a population or sample. The population in this study were all students of class X SMK Muhammadiyah 01 Sambi academic year 2015/2016 with a sample of 90 students with simple random sampling or random. The data required in the study was obtained through a questionnaire and documentation. Before the questionnaire used first tested the validity and reliability. Data analysis technique used is multiple linear regression analysis, t-test, f, as well as the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 23.653 + 0,217X1 + 0,219X2. The conclusion that can be drawn from this equation are: 1) "There is the influence of teachers' communication capabilities to the satisfaction of learning" is acceptable. This is proven by testing hypotheses (t test) in which it is known that tcount> ttable, namely 2.877> 1.988 or sig. <0.05 is 0.005 with the effective contribution of 7.3%. 2) "There is the influence of active students to the satisfaction of learning" is acceptable. This is based on test hipoteisi (t test) which can be seen that tcount> ttable namely 2.660> 1.988 or sig. <0.05 is 0.009, the effective contribution of 6.1%. 3) "There is the influence of communication skills of teachers and learning activeness together to satisfaction of learning" is acceptable. This is based on test f the linkage that Fhitung> Ftabel namely 6.755> 3.10 or sig. <0.05 is 0.002. 4) The result of the coefficient of determination (R2) of 0.134 which indicates that the influence of communication skills teacher and student activity amounted to 13.4%, while the remaining 86.6% is influenced by other variables not examined by investigators.